Pengaruh Tingkat Pendidikan, Pelatihan, dan Pengalaman Mengajar terhadap Profesionalitas Guru di Madrasah Tsanawiyah Negeri Kediri 2 - Firdaus, Daniatul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2014)
This study examines the influence of educational levels, training and teachingexperiences towards professionalism of teachers at MTs Negeri Kediri 2. Byusing quantitative approach, the study revealed the following results. Firstly, thelevel of education of teachers at MTsN Kediri 2 is high. Secondly, the teachertraining followed by teachers at MTsN Kediri 2 can be classified as moderate.Thirdly, the teaching experience of teachers at MTsN Kediri 2 can also beclassified as moderate. Fourthly, the professionalism of teachers at MTsN Kediri2 can be classified as moderate. Fifthly, the educational level of teachers at MTsNKediri 2 affects the professionalism of teachers by 21.6 %. Sixthly, the teachertraining affects the professionalism of teachers by 21.6 %. Seventhly, the teachingexperience affects the professionalism of teachers by 13.3 %. Finally, the levelof education , training and teaching experience affect the professionalism ofteachers by 34.5 %.